Central Obesity Analysis from the Aspect of Risky Foods and Food Consumption Patterns Related to Cultural Systems: The 2023 SKI Study - Hartono Hadjarati; Nasrun Pakaya; Widy Susanti Abdulkadir; Edy Dharma Putra Duhe; Oktia Woro Kasmini Handayani (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
In Indonesia, central obesity among people aged 15-54 years has become a health problem that continues to increase from 2018 (30.8%) to 2023 (36.8%) and significantly contributes to degenerative diseases. This study aims to analyze dietary patterns and consumption of risky foods related to central obesity in Indonesia using a spatial analysis approach. Data are sourced from the 2023 Indonesian Health Survey (SKI) Report with 38 provinces as the analysis unit. The variables studied include consumption of risky foods (sweet foods and drinks, salty foods, markers, seasonings, and instant noodles) and consumption patterns of foods such as nuts, milk, sugar, oil, vegetables, and fruit. Data analysis was carried out using Moran’s I and Local Indicator of Spatial Autocorrelation (LISA) to identify spatial autocorrelation and Ordinary Least Squares (OLS) as the regression analysis. The results show that the incidence of central obesity in Indonesia forms a clustered pattern across provinces. OLS regression analyzed the main variables that were significantly related, namely consumption of salty foods, fried/fatty foods, nuts, and vegetables and fruit. The negative association between salty foods and nuts is explained by local cultural factors and relatively low-calorie consumption, while the positive association between fruit and vegetable consumption indicates low consumption frequency, thus suboptimal preventive factors for central obesity. These findings demonstrate the need for community nutrition interventions that consider spatial variation across provinces to improve the effectiveness of central obesity prevention efforts in Indonesia.